Heritability estimate for stayability in nelore cows - Silva, JAIIV; Eler, J. P.; Ferraz, JBS; Golden, B. L.; Oliveira, H. N. (Elsevier B.V., 2003)
The objective of the present study was to determine the possibility of using stayability (STAY) of dams as a selection criterion for fertility in the Nelore breed. STAY was defined as whether or not a cow calved in a herd at a specific age or after this age given that she had calved at an earlier age. The specific ages studied were 5 (STAY5), 6 (STAY6) and 7 (STAY7) years. Data on 53 271, 46 011 and 41517 animals were analyzed for the respective ages. The Method 91 was used to estimate the variance components and a maximum threshold a posteriori model was used to predict the genetic values. The analyses provided h(2) estimates of 0.117+/-0.003, 0.122+/-0.004 and 0.171+/-0.005 for STAY5, STAY6 and STAY7, respectively. The ease with which the trait can be recorded and the h 2 estimates indicate that the use of this trait as a selection criterion can contribute to increased dam fertility. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: cattle-genetics; method R; reproductive trait; survival; threshold model